RELASI-KONFLIK SUKU QURAISH DAN BANI MUSTALIQ DI ERA NABI MUHAMMAD - Sulthon, Muhammad (Jurnal THEOLOGIA, 2012)
This paper examines the role of the prophet Muhammad's preaching in resolving internal conflicts of Quraysh tribe and conflicts between the Quraysh tribe with a descendant of Mustaliq. The goal is to reconstruct their conflicts and Muhammad's position in the middle of the conflict. For that purpose, the data collected from the books of Sirah Nabawiyah as the main source and analyzed so that it can be drawn the conflict relationship between the two tribes and the resolution. The results of the study found the conflict between the Quraysh tribe of the descendant of Mustaliq can be tracked since their ancestors, respectively, before the advent of Muhammad. Fundamental issues regarding with conflicts dealing with political power, self-esteem and group identity. The triggers of conflict that almost rising the violent conflicts between the other were a misunderstanding. In resolving the conflict, the prophet prefers peaceful means despite ever using violence in the form of war.Tulisan ini mengkaji peran dakwah nabi Muhammad dalam menyelesaikan konflik intern suku Quraish maupun konflik antara suku Quraish dengan bani Mustaliq. Tujuannya, merekonstruksi relasi konflik antara mereka dan posisi Muhammad di tengah tengah konflik tersebut. Untuk tujuan itu, data dihimpun dari kitab-kitab Sirah Nabawiyah sebagai sumber utama dan dianalisis sehingga tergambar relasi-konflik tokoh-tokoh dari kedua suku tersebut dan penyelesaiannya. Hasil kajian menemukan, konflik antara suku Quraish dengan bani Mustaliq dapat dilacak sejak nenek moyang mereka masing-masing, sebelum kenabian Muhammad. Issu pokok terjadinya konflik berkenaan dengan persoalan politik kekuasaan, harga diri dan identitas kelompok. Pemicu konflik yang nyaris menimbulkan kekerasan antara lain adalah kesalahpahaman. Dalam menyelesaikan konflik, nabi lebih mengutamakan jalan damai meski pernah menggunakan kekerasan dalam bentuk peperangan